From QitÄl to DifÄâ€™: The Meaning and Behavior of Jihad according to Jihadists in Semarang City - Lathifah, Anthin (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2018)
This paper describes the meaning and act of religion-based jihad according to some jihadists in Semarang city. Insisting that the real meaning of Jihad is qitÄl (war, to fight) as said by the verse â€œLa hukma Illa lillahâ€ and hadith â€œfaqtulÅ« haythu wajadtumÅ«humâ€ they, however, still propose another jihad called difÄâ€™ (defensive, to survive) for people who cannot meet the requirement of qitÄl. The different act of jihad emerges because of its different factors behind such as social, economy, politics, psychology and others. The shift from qitÄl to difÄâ€™ takes place by the process of humanizing the jihadists using: 1) personal approach by their morally closest men; 2) basic need approach such as economy, existency and peace; 3) religious approach by understanding that what they do is to fully adhere to Islam (kaffah); 4) emotional approach by caring and giving them empathy; 5) social approach by building solidarity to help their comrades.[]Artikel ini mendeskripsikan makna dan perilaku jihad dari para pelaku jihad berbasis agama di Kota Semarang. Makna jihad yang sebenarnya bagi mereka adalah qitÄl sebagaimana ayat â€œla hukma illa lillahâ€ dan hadits â€œfaqtulÅ« haythu wajadtumÅ«humâ€, namun jihad difÄâ€™ dapat dilakukan bagi yang tidak memenuhi syarat jihad qitÄl. Perbedaan perilaku jihad terjadi karena perbedaan faktor yang melingkupinya, yakni faktor sosial, ekonomi, politik, psikologi dan lainnya. Perubahan perilaku jihad (qitÄl) menjadi difÄâ€™ terjadi karena proses memanusiakan manusia yang dilakukan dengan: 1) pendekatan personil yang dilakukan oleh orang yang dekat secara moril; 2) pendekatan berbasis kebutuhan primer mereka baik ekonomi, eksistensi ataupun rasa aman; 3) pendekatan agama dilakukan dengan memahami apa yang mereka lakukan adalah dalam rangka melakukan Islam secara kaffah; 4) pendekatan emosional dengan memberi perhatian atau empati; 5) pendekatan sosial dengan membangun solidaritas untuk membantu teman-teman seperjuangannya.